Beyond European unemployment insurance. Less moral hazard, more moral assurance? - Günther Schmid (Transfer: European Review of Labour and Research, 2020)
The compromise that emerged from the lengthy debate on European unemployment insurance (EUI) involved the establishment of a `European Unemployment Reinsurance Scheme'. However, it was not until the shock waves of the COVID-19 pandemic were felt that any specific measures were actually taken to establish such a scheme. The reasons for such prevarication were, first, doubts as to whether moral hazard can be kept under control and, second, the huge diversity of EU Member States' coverage and level of social protection. This article offers a third reason for this protracted stalemate: the neglect of moral assurance as a countervailing force of moral hazard. It argues that the concept of unemployment insurance itself needs to be fundamentally revised. Modern labour market policy must cover not only income risks related to unemployment, but also other serious income risks related to critical transitions over the life course. Finally, this article proposes the extension of the European Social Fund to create a European Employment and Social Fund with elements of work-life insurance and a reinsurance mechanism for shock absorption. – – Le compromis qui a émergé du long débat sur l'assurance-chômage européenne (EUI) impliquait la création d'un “régime européen de réassurance-chômage”. Il a néanmoins fallu attendre les ondes de choc de la pandémie du COVID-19 pour voir apparaître des mesures spécifiques visant à mettre en place un tel système. Ces hésitations étaient liées, d'une part, aux doutes quant à la possibilité de maîtriser l'aléa moral et, d'autre part, à la grande diversité de la couverture et du niveau de protection sociale dans les États membres de l'UE. Cet article propose une troisième raison à cet enlisement prolongé : le fait de négliger l'assurance morale comme contrepoids à l'aléa moral. L'auteur soutient que le concept d'assurance-chômage lui-même doit être fondamentalement révisé. La politique moderne du marché du travail doit couvrir non seulement les risques de revenus liés au chômage, mais aussi d'autres risques de revenus, importants et liés à des transitions critiques au cours de la vie. Enfin, l'article plaide en faveur d'un élargissement du Fonds social européen, avec la création d'un Fonds social et de l'emploi européen qui comporterait des éléments d'assurance vie-travail et un mécanisme de réassurance destiné à absorber les chocs.
Keywords: 330; European Union; European Social Fund; unemployment insurance; social insurance; moral hazard; moral assurance; transitional labour markets; work-life insurance